Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Changer de sexe: identités transsexuelles - Augst-Merelle, Alexandra; Nicot, Stéphanie (Cavalier bleu, 2006)
Rédigé par deux transgenres, un portrait de la communauté transexuelle française qui fait justice des préjugés et s'efforce de balayer toutes les idées reçues.
Section: 187, [4] pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; militance; premier cycle; périodes historiques; queer; queer of color; régions géographiques; shm4000; systèmes d'oppressions; thématiques; transféminisme

Queer zones: politique des identités sexuelles et des savoirs - Bourcier, Marie-Hélène (Amsterdam, 2006)
Publié pour la première fois en 2001, ce livre pionnier a permis l'ouverture d'un espace théorique et politique queer en France. Il s'agit d'une boîte à outils destinée aux activistes en quête de cultures et de politiques sexuelles qui ne soient pas (homo ou hétéro) normatives. Stimulants et provocants, les textes réunis dans ce recueil constituent également une introduction critique à la déconstruction des genres et aux travaux de Judith Butler et de Michel Foucault. Ils mettent de plus en évidence l'apport des subcultures trans, butch et SM à une réflexion plus large sur les relations entre pouvoir et savoir, ainsi que le formidable potentiel des sexualités dissidentes et la continuité politique entre féminisme pro-sexe et activisme queer. Cette nouvelle édition comprend trois essais inédits sur le " devenir femme " de Deleuze, l'utopie sexuelle urbaine de Gayle Rubin et la post-pornographie selon Annie Sprinkle.
Keywords: approches et analyses; cours; discipline; fem1000; har4600; histoire; identités LGBTQIA2+; lit3220; militance; personnes trans*; politique; premier cycle; queer; sciences humaines; sexualité; thématiques; violences

Crip theory: cultural signs of queerness and disability - MacRuer, Robert (New York University Press, 2006)
A bold and contemporary discourse of the intersection of disability studies and queer studies Crip Theory attends to the contemporary cultures of disability and queerness that are coming out all over. Both disability studies and queer theory are centrally concerned with how bodies, pleasures, and identities are represented as “normal” or as abject, but Crip Theory is the first book to analyze thoroughly the ways in which these interdisciplinary fields inform each other. Drawing on feminist theory, African American and Latino/a cultural theories, composition studies, film and television studies, and theories of globalization and counter-globalization, Robert McRuer articulates the central concerns of crip theory and considers how such a critical perspective might impact cultural and historical inquiry in the humanities. Crip Theory puts forward readings of the Sharon Kowalski story, the performance art of Bob Flanagan, and the journals of Gary Fisher, as well as critiques of the domesticated queerness and disability marketed by the Millennium March, or Bravo TV’s Queer Eye for the Straight Guy. McRuer examines how dominant and marginal bodily and sexual identities are composed, and considers the vibrant ways that disability and queerness unsettle and re-write those identities in order to insist that another world is possible.
Section: 283 pages : illustrations
Keywords: EDI; LGBTQIA2+; approches et analyses; art; cours; crip; discipline; militance; premier cycle; queer; santé; soc2014; thématiques; études critique du handicap; études littéraires

Daniel Guérin et le discours militant sur l'homosexualité masculine en France (années 1950-années 1980) - Marchant, Alexandre (Revue d’histoire moderne & contemporaine, 2006)
Daniel Guérin (1904-1988), intellectuel marxiste et militant anarchiste, est un révélateur pour mesurer certaines transformations des représentations sociales de l’homosexualité en France, des années 1950 aux années 1980. Guérin incarne le passage d’un univers de discours (au sens de modèles de communication) à un autre,du légalisme arcadien à la perspective révolutionnaire du FHAR;de la discrétion à la politisation. Il a développé une pensée théorique originale de l’homosexualité, en rabattant celle-ci sur une bisexualité originelle. Sa réflexion sur les transformations sociales et historiques de l’identité homosexuelle inscrit la question des identités sexuelles dans une perspective nominaliste. Dans les années 1950 et 1960, les écrits de Guérin traitent de la répression de l’homosexualité en France. L’auteur donne également un éclairage particulier à la question de la révolution sexuelle des années 1970. Ses interventions littéraires ou publiques, dont la forme varie selon les contextes et les époques, ont encouragé la revendication politique d’une homosexualité stigmatisée juridiquement et réprimée policièrement.Néanmoins,de la fin des années 1970 à sa mort, il a durement critiqué l’essentialisation progressive de l’homosexualité au rang de marqueur identitaire.
Keywords: 1900-1999; EDI; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours militant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; identités LGBTQIA2+; justice sociale; marxisme; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

Hygiène et modernisation - Ross, Kristin (Rouler plus vite, laver plus blanc : modernisation de la France et décolonisation au tournant des années 60, 2006)
Keywords: 1900-1999; 1950-1959; changement social; cours; discipline; europe; fem1000; france; histoire; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques